How bio-inspired solutions have influenced the built environment design in hot and humid climates - Solano, Thasnee; Bernal, Ana; Mora, Dafni; Chen Austin, Miguel (Frontiers in Built Environment, 2023)
The rapid increase in the population, which has been concentrated mainly in urban areas, has caused an environmental imbalance over the years since the built environment developed as a foreign element to the ecosystem, which prevents having resilient environments capable of adapting to the challenges posed by climate change. This research aims to provide an updated knowledge base of bio-inspired strategies emulated in hot and humid climates to achieve an efficient built environment, restoring resources, and bringing nature closer to cities. A systematic review is conducted based on keyword selection to answer (i) what has been achieved in built environments to be more efficient and sustainable (including tropical climates) and (ii) how natural patterns, strategies, and models are mimicked. Implementing these strategies is very little in regions with hot and humid climates. Bio-inspired approaches are concentrated in those that try to emulate the functions of nature, followed by approaches that imitate the form of nature, biomimicry, and biomimetics being the most used approaches, leading to the development of efficient and resilient cities.